Evaluating the impact of ultraviolet light on chemical and mechanical properties of human scalp hair through controlled and natural experiments - Buthelezi, Ntandoyenkosi (Department of Medicine, 2025)
Introduction: Human hair fibres have been studied in a variety of fields for different applications. Examples include the use of hair as a medical testing substrate for diagnosis of pathologies, as a tool for forensic investigations, a substrate for cosmetic product development and as a precursor material for construction engineering and agriculture. The changes that affect the character and behaviour of hair fibres, arising from exposure to environmental factors such as UV radiation, have been the focus of some studies. Even though there are a range of environmental variables that could be worthy of consideration, understanding the impact of UV radiation is increasingly important given the inevitability of exposure and changes in climatic conditions. Chemical and mechanical experiments have demonstrated that the proteins and pigments of human hair are most heavily affected during exposure to UV radiation, resulting in unhealthy fibres, suppressed growth and permanent hair loss. Problem: Photodamage and photoprotective potential of human hair fibres have been identified, however many studies have been conducted on ‘Caucasian' hair samples and the findings have been assumed to hold for other population groups. The use of race-based classification systems has further confounded findings, as the groupings are not able to account for intra-population and intra-individual variation objectively. This study is the first evaluation aimed at comparing the effect of UV radiation on hair of varying curl, using a combination of chemical and mechanical tools alongside advanced statistical techniques on the same samples. Furthermore, the study makes use of both controlled UV-exposed fibres and dreadlocks exposed to natural sunlight. Therefore, this study aims to compare the effects of UV irradiation and hair curl on the chemical and mechanical characteristics on human hair fibres, for controlled UV-exposed fibres and natural sun-bleached dreadlocks. Method: To analyse the influence of the radiation interaction with human hair, natural untreated, and UVA and UVB radiated black hair samples of low to high curl were compared. This study utilized thermogravimetric analysis and derivative thermogravimetry (TGA/DTG), Fourier-transform infrared spectrometry (FTIR- ATR) coupled with multivariate analysis, scanning electron microscopy (SEM) and mechanical tensile testing (MTT) techniques to obtain information on the chemical, and mechanical properties of the human hair. Results: UVB radiation resulted in more significant changes than UVA across all curl types, as demonstrated by all measurement techniques. After 7 days of UVB exposure, FTIR revealed changes on the absorbance of the amide and lipid bands. Major changes were observed associated with degradation of proteins at characteristic peaks; amide A (3300 and 3070 cm-1 ), amide I (1650 cm-1 ), and amide II (1550 cm-1 ). UVB 7-days exposure also produced the highest amount of the cystine oxidation products (at 1022-1077 cm-1 region) and had the lowest absorption for the disulphide bonds. The TGA/DTG showed that the onset degradation temperature (ODT) of UVB-treated fibres was significantly reduced compared to both the control group and UVA exposed group. The MTT results showed increased yield stress and yield strain for UVB exposed fibres. Interestingly, a threshold effect in damage was observed in low curl fibres as opposed to high curl fibres. Extending UV exposure time beyond 7-days in low curl hair fibres did not result in increased damage, however, this phenomenon was not observed for the high curl fibres. For the natural dreadlock experiment, the distal hair fibres showed reduced thermal stability and changes in the chemical properties observed on the FTIR. There were no significant changes on the mechanical properties of proximal compared to distal hair fibres. However, a SEM investigation revealed more structural damage in the distal fibres which might contribute to differences observed in the TGA and FTIR. This study provides novel insight into a critical point at which damage becomes pronounced and highlights how hair fibres of varying curl respond to UV-induced stress. This knowledge will not only aid hair scientists in navigating population specific hair analysis, but also provides valuable insights and paves a way for informed strategies for hair care development industry and related disciplines. The results obtained in this study could be beneficial for the hair care industry by informing the formulation of targeted products that account for different hair types and their specific vulnerabilities to UV damage. For instance, cosmetic companies could develop specialized UV protection shampoos and conditioners designed to address the specific needs to different hair types.